Converging hybrid worlds? : medicine and hospital management in Europe - Bode, Ingo; Dent, Mike (International Journal of Public Sector Management: Volume 27, Issue 5., 2014)
This ebook, delving into the institutional and procedural contingency shaping the evolution of managerial arrangements across Europe, contains four articles on national configurations, one comparative paper, and one conceptual contribution. The papers included in this ebook provide us with illustrative examples of the rich range of the variation in medical hybridization that is, and in some cases, is not going on within the hospitals across Europe. The 'managerialisation' in hospital care that has blurred the boundaries between medicine, management and clinical leadership exhibits a national c.